Emprego da RMN HR-MAS e análises quimiométricas no reconhecimento e avaliação de soja (Glycine max) geneticamente modificada - Barison, Andersson (Universidade Federal de São Carlos, 2005)
The Biotechnology has made possible the development of genetically modified (GM) organisms, including soybean, main Brazilian agricultural product. These GM specimens has been produced by changing some original characteristics of plant in order to increase productivity and to reduce production costs. However, these novel organisms should be evaluated, in order to verify its safety for environment and human and animal consume. In this context, it is necessary to develop new analytical methodologies for substantial equivalence determination of these novel plants. NMR is an important analytical tool allowing acquisition of a great number of chemical information in a single experiment. Within NMR techniques, HR-MAS makes possible direct acquisition on intact samples (In situ), without any sample treatment. In addition, chemometric analysis is a powerful tool, which allows interpretation of high complex data, such as NMR spectra. In this work, HR-MAS NMR has been employed for acquisition of NMR spectra directly of soybeans and leaves. Application of chemometric analysis on NMR data, has made possible to discriminate samples according to cultivar, geographic origin and mainly genetic origin, as well as to predict the identity of unknown samples by means of classification models. For this, all methodology, including HR-MAS NMR spectra measurements and chemometric analysis, was developed and optimized. Chemometric analysis performed on HR-MAS NMR spectra has also allowed to determine differences on chemical composition among samples, mainly those between traditional and GM specimens, giving important information about substantial equivalence of GM soybean crops. In conclusion, it has been demonstrated that HR-MAS NMR technique together with chemometric analysis is an important tool to be used in metabolomic studies and in quality control of agricultural products.
APPLICATION OF HR-MAS NMR AND CHEMOMETRIC ANALYSIS FOR DETECTION AND EVALUATION OF GENETICALLY MODIFIED SOYBEAN (Glycine max) CROPS
Keywords: Ressonância magnética nuclear; RMN HR-MAS; Quimiometria; Soja; Soja geneticamente modificada; CIENCIAS EXATAS E DA TERRA::QUIMICA